Commentary on the law of the International Criminal Court : The Satute - Klamberg, Mark, editor; Nilsson, Jonas, editor; Angotti, Antonio, editor (Brussels : Torkel Opsahl Academic EPublisher, 2023)
The Commentary on the Law of the International Criminal Court (CLICC) provides a provision-by-provision analysis of the Rome Statute and the Rules of Procedure and Evidence of the International Criminal Court
Includes bibliographical references.
Keywords: International Criminal Court; Public international law; International criminal law; Rules of Procedure and Evidence